(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Considers the features of the automated design of technological processes of assembly of products in mechanical engineering, in terms of their impact on production processes.